Insights on the association between somatic aneuploidy and ostreid herpesvirus 1 detection in the oysters Crassostrea gigas, C. angulata and their F1 hybrids - Batista, Frederico M.; Lopez-sanmartin, Monserrat; Boudry, Pierre; Navas, Jose I.; Ruano, Francisco; Renault, Tristan; Fonseca, Vera G.; Leitao, Alexandra (Aquaculture Research, 2016)
Cytogenetic abnormalities associated with viral infections, including from viruses of the Herpesvirales order, have been reported in vertebrate species. Ostreid herpesvirus 1 (OsHV-1) has been detected worldwide during mortality outbreaks of the Pacific oyster Crassostrea gigas. On the other hand, a high proportion of aneuploid cells in somatic tissues have been observed in C. gigas. In this study, we analysed the putative association between aneuploidy levels and the detection of OsHV-1 in gills of C. gigas, the Portuguese oyster C. angulata and their F1 hybrids cultured in Ria Formosa (Portugal). OsHV-1 was detected by PCR in 5.4% of the total of oysters analysed (n = 111) namely in 11.1%, 8.0% and 1.7% of C. gigas, C. angulata and F1 hybrid respectively. Sequencing analysis of a viral fragment amplified with the C2/C6 primer pair revealed a high similarity with the OsHV-1 reference type. Moreover, in situ hybridization confirmed the presence of OsHV-1 in gill tissue. Oysters where OsHV-1 was detected had a significantly higher mean percentage of aneuploid cells (25%) than the ones where the virus was not detected (18%). However, the overall low percentage of positive samples contrasted with the high mean percentage of aneuploidy observed, with 50% of the oysters analysed showing a percentage of aneuploid cells between 20% and 30%. We hypothesize that somatic aneuploidy may adversely affect oysters making them more prone to OsHV-1 infection, but the virus is unlikely to be the cause of somatic aneuploidy.